7(1-3v)=7v+7

Simple and best practice solution for 7(1-3v)=7v+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(1-3v)=7v+7 equation:


Simplifying
7(1 + -3v) = 7v + 7
(1 * 7 + -3v * 7) = 7v + 7
(7 + -21v) = 7v + 7

Reorder the terms:
7 + -21v = 7 + 7v

Add '-7' to each side of the equation.
7 + -7 + -21v = 7 + -7 + 7v

Combine like terms: 7 + -7 = 0
0 + -21v = 7 + -7 + 7v
-21v = 7 + -7 + 7v

Combine like terms: 7 + -7 = 0
-21v = 0 + 7v
-21v = 7v

Solving
-21v = 7v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-7v' to each side of the equation.
-21v + -7v = 7v + -7v

Combine like terms: -21v + -7v = -28v
-28v = 7v + -7v

Combine like terms: 7v + -7v = 0
-28v = 0

Divide each side by '-28'.
v = 0

Simplifying
v = 0

See similar equations:

| 1-cosx=sinx | | 343x^3-1000=0 | | 4x+3(x-2)=2x+14 | | 20(x+y)=20x+y | | 2z*2z+2=48 | | 3t^3-3t^2=36t | | -ln(-ln(4))=c | | B^2+9=64 | | 26(5-4x)+23(7-3x)+11=22(5-4x)+19(7-3x)+3 | | 12x^2-66x+16=0 | | 6(x-2)=2-2(-5x+5) | | -2x=-4x | | -8t-6t-6-8t= | | B^2+6=64 | | 4x-17=81 | | 2/11-3/11x=2 | | 4t-26=70 | | (3x)(2x+8)=0 | | 15x-3x-18=6 | | 5x^2-2x+0=0 | | 6x-4/7=2 | | -62=4(1+3r)+6 | | 100x-11x^2-6=0 | | 2-3x/11=2 | | 8sin^2x+6sinx-9=0 | | 1(x+3)=1x-4 | | g(x)=160x+50 | | y=2x^2+24x+79 | | (2)^1/2 | | -1/9(27a-81)-24 | | 3(-1x+6)=33 | | ax=x+6 |

Equations solver categories